Lasersko varjenje kontaktov okova žarnice E27 - Juvan, Matej (Materiali in tehnologije, 2003)
The manufacturing of lamp holders has been made more economic with the remodelling of holder contacts and the introduction of low-strength basic material in the production process. We achieved the desired compactness/solidity of the contacts with additional welding of the twisted part junction. Only methods with precise localization of the weld, simple automation of the process and no additional product remodelling are useful. Welding with a Nd-YAG laser source is one such method.We developed a low-cost system for laser welding of E27 lamp-holder contacts. The system construction enables a direct upgrade of the existing production line. In the present article we deal with the development of the system and the results of the test operation.
Keywords: varjenje točkovno; varjenje lasersko; pločevina jeklena; laserji Nd-YAG; vlakna optična; lasersko varjenje; točkovno varjenje; jeklo; proizvodnja